2021
DOI: 10.1021/acsmedchemlett.1c00155
|View full text |Cite
|
Sign up to set email alerts
|

SD-91 as A Potent and Selective STAT3 Degrader Capable of Achieving Complete and Long-Lasting Tumor Regression

Abstract: Signal transducer and activator of transcription 3 (STAT3) is an attractive cancer therapeutic target. We report herein our extensive in vitro and in vivo evaluations of SD-91, the product of the hydrolysis of our previously reported STAT3 degrader SD-36. SD-91 binds to STAT3 protein with a high affinity and displays >300-fold selectivity over other STAT family protein members. SD-91 potently and effectively induces degradation of STAT3 protein and displays a high selectivity over other STAT members and >7000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 13 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…In subsequent studies, they found that SD-36 hydrolyzed and converted its difluoro methylene group to a ketone group under different conditions in vitro and in vivo , and the conversion rate in an alkaline environment was much faster than that in acidic conditions. 184 After confirming the conversion mechanism, they tested the degradation activity of the converted degrader SD-91 (Fig. 15), and found that the degrader SD-91 showed excellent stability in different drug delivery systems.…”
Section: Design Of Typical Protacsmentioning
confidence: 98%
“…In subsequent studies, they found that SD-36 hydrolyzed and converted its difluoro methylene group to a ketone group under different conditions in vitro and in vivo , and the conversion rate in an alkaline environment was much faster than that in acidic conditions. 184 After confirming the conversion mechanism, they tested the degradation activity of the converted degrader SD-91 (Fig. 15), and found that the degrader SD-91 showed excellent stability in different drug delivery systems.…”
Section: Design Of Typical Protacsmentioning
confidence: 98%
“…Some of them (e.g. STAT3) have been reviewed elsewhere, [79][80][81][82][83] here we discuss some more recently published examples.…”
Section: Expanding Target Space For Protein Degradationmentioning
confidence: 99%
“…In our previous study, we showed that an indole-based phosphotyrosine mimetic was critical for our development of potent and cell-permeable STAT3 degraders . However, the indole-based phosphotyrosine mimetic was later found to have a chemical stability issue where difluoro carbon moiety in the indole-based phosphotyrosine mimetic gradually decomposes to form ketone . To overcome this issue, we carried out extensive modification of the indole-based phosphotyrosine mimetic and identified other phosphotyrosine mimetics with excellent chemical stability, including a benzothiophene-based phosphotyrosine mimetic .…”
Section: Resultsmentioning
confidence: 99%